Imaging in Periprosthetic Joint Infection Diagnosis: A Comprehensive Review - Armin Hoveidaei; Yasaman Tavakoli; Mohammad Reza Ramezanpour; Mahyaar Omouri-kharashtomi; Seyed Pouya Taghavi; Amir Human Hoveidaei; Janet D. Conway (Microorganisms)
Various imaging methods assist in diagnosing periprosthetic joint infection (PJI). These include radiological techniques such as radiography, computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound (US); as well as advanced nuclear medicine techniques including bone scintigraphy (BS), anti-granulocyte antibody imaging (AGS), leukocyte scintigraphy (LS), and fluorodeoxyglucose positron emission tomography (FDG-PET and FDG-PET/CT). Each imaging technique and radiopharmaceutical has been extensively studied, with unique diagnostic accuracy, limitations, and benefits for PJI diagnosis. This review aims to detail and describe the most commonly used imaging techniques and radiopharmaceuticals for evaluating PJI, focusing particularly on knee and hip arthroplasties.